Geothermal regime and implications for basin resource exploration in the Qaidam Basin, northern Tibetan Plateau. (November 2022) - Pang, Yumao; Zou, Kaizhen; Guo, Xingwei; Chen, Yan; Zhao, Jian; Zhou, Fei; Zhu, Jun; Duan, Lifeng; Yang, Guoxin
Graphical abstract: Highlights: Geothermal field characteristics of the Qaidam Basin, northeastern Tibetan Plateau, were analysed. The crustal contribution to the surface heat flow was approximately 55%. The existence of abnormally high-temperature zones significantly dominated the hydrocarbon distribution. The Qaidam Basin is favourable for low- and medium-temperature geothermal resources development. Certain deep high-temperature geothermal resource is prospective if using abandoned oil wells. Abstract: The Qaidam Basin was formed under the background of the continuous uplift of the Tibetan Plateau, and its tectonic location imparts unique geothermal regime. The geothermal regime of the Qaidam Basin was studied based on oil-test static temperatures from 60 wells, 195 thermal conductivities measured by the optical scanning method, and 142 radiogenic heat production values. The geothermal gradient in the Qaidam Basin is 17.1–47.6 °C/km, with an average of 31.3 °C/km, and the thermal conductivity is 0.523–4.379 W/m‧K. The heat flow is 28.3–83.1 mW/m 2, with an average of 59.6 mW/m 2, and it is "high in the west and low in the east." The heat flow can exceed 70 mW/m 2 in the northern marginal fold-and-thrust belt of western Kunlun and Nanyishan and generally exceeds 65 mW/m 2 in the Mangya Depression. The average radiogenic heat production rate (HPR) is 2.53 μW/m 3, which is close to the HPR of granite in northern Tibetan Plateau. The crustal and mantle heat flows in the Qaidam Basin are 32.9 mW/m 2 and 26.7 mW/m 2, respectively. The crustal contribution to the surface heat flow was approximately 55 %. The geothermal regime may be dominated by lithospheric thickness, HPR of sedimentary cover, and extra heat production related to late Cenozoic tectonic movement. The proven hydrocarbon reserves are primarily distributed around hydrocarbon-generating kitchens, and the existence of abnormally high-temperature zones significantly influences hydrocarbon distribution. The Qaidam Basin satisfies the fundamental temperature conditions for the development of low- and medium-temperature geothermal resources using abandoned oil and gas drilling wells.